Coexisting transport behaviors in quasibinary Cd(3 − 3m)Ga2mTe3 (m = 0.75–0.98) system with structural vacancy and cationic interdiffusion. (1st March 2016) - Liu, Haiyun; Tian, Dingqi; Du, Zhengliang; Cui, Jiaolin
Abstract: In Ga2 Te3 -rich quasibinary Cd(3 − 3 m ) Ga2 m Te3 ( m  = 0.75–0.98) system there are two physical phenomena: structural vacancy ( V ) and its related cationic interdiffusion. The former is able to simultaneously govern the carrier, phonon transportations and the bandgap, while the latter merely facilitates the transportation of carrier to some extent. Accordingly, there are multiple transportation behaviors coexisting at a certain m value in this system. These behaviors, which have not only enhanced the carrier concentration ( n ), but have also increased the entropy of the lattice as m value increases, yield the highest thermoelectric figure of merit ( ZT ) of 0.55 at 682 K for m  = 0.98. Graphical abstract: Cationic interdiffusion related to structural vacancies and a thermoelectric figure of merit of ZT = 0.55 at 682 K in Cd(3 − 3 m ) Ga2 m Te3 system.